2020
DOI: 10.1002/cti2.1171
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose post‐transplant cyclophosphamide impairs γδ T‐cell reconstitution after haploidentical haematopoietic stem cell transplantation using low‐dose antithymocyte globulin and peripheral blood stem cell graft

Abstract: Objectives Haploidentical haematopoietic cell transplantation (Haplo‐HCT) using peripheral blood stem cell (PBSC) grafts and post‐transplant cyclophosphamide (PTCy) is being increasingly used; however, data on immunological reconstitution (IR) are still scarce. Methods This retrospective study evaluated T‐cell immunological reconstitution in 106 adult patients who underwent allogeneic haematopoietic cell transplantation for haematologic malignancies between 2013 and 2016. Results At D30, while conventional T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Recent works provide a promising option by optimizing ATG dosing (2.5 mg/kg daily for 3 days) to reduce viral activation while maintaining sufficient GvHD prophylaxis in haplo-HSCT ( 45 , 46 ). Similar phenomena were observed in haplo-HSCT using a combination of post-transplantation cyclophosphamide and low-dose ATG ( 47 , 48 ). A lower dose of ATG (2.5 mg/kg) successfully reduces CMV reactivation without compromising the favorable effect of preventing GvHD ( 49 ).…”
Section: Discussionsupporting
confidence: 72%
“…Recent works provide a promising option by optimizing ATG dosing (2.5 mg/kg daily for 3 days) to reduce viral activation while maintaining sufficient GvHD prophylaxis in haplo-HSCT ( 45 , 46 ). Similar phenomena were observed in haplo-HSCT using a combination of post-transplantation cyclophosphamide and low-dose ATG ( 47 , 48 ). A lower dose of ATG (2.5 mg/kg) successfully reduces CMV reactivation without compromising the favorable effect of preventing GvHD ( 49 ).…”
Section: Discussionsupporting
confidence: 72%
“…Of note, their reconstitution does not appear to be dependent on conditioning intensity ( 118 ), however, γδ T cells appear extremely sensitive to PTCy in the setting of haploidentical transplantation. In this setting, γδ, and especially the Vδ2 + T‐cell counts were significantly lower in the early post-transplantation period ( 131 , 132 ). This effect on the Vδ2 + cell population persisted for up to one year post-transplantation and correlated with more frequent EBV reactivation ( 131 ).…”
Section: γδ T Cellsmentioning
confidence: 77%
“…In this setting, γδ, and especially the Vδ2 + T‐cell counts were significantly lower in the early post-transplantation period ( 131 , 132 ). This effect on the Vδ2 + cell population persisted for up to one year post-transplantation and correlated with more frequent EBV reactivation ( 131 ).…”
Section: γδ T Cellsmentioning
confidence: 77%
“… 36,37 Combining ATG with PT-Cy can induce a significant reduction in early gamma-delta (γδ) T-cell proliferation, and is associated with a higher risk of increase in EBV viral loads. 38 However, the impact of such a delayed lymphocyte reconstitution on HHV6 reactivation has scarcely been studied. Two previous studies have reported a protective effect of higher lymphocyte counts (CD3+ lymphocytes ≥ 200/µL) against HHV6 reactivation.…”
Section: Discussionmentioning
confidence: 99%